SYARAT SUBJEKTIF SAHNYA PERJANJIAN MENURUT KITAB UNDANG-UNDANG HUKUM PERDATA (KUH PERDATA) DIKAITKAN DENGAN PERJANJIAN E-COMMERCE - Vinayanti Bumi, Shinta; Sri Indrawati, Anak Agung (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 03, Mei 2013)
When we are dealing with e-commerce agreements, we have to remember that thiskind of agreement is unknown in Indonesian Civil Code. The possible thing that mightcross through our mind is the legal subjective requirements for this kind of agreementbased on the Indonesian Civil Code in its relation to e-commerce agreement. Theseagreements are emerging as a result of information and technology development. Anypeople can enter into a business agreement through electronic communication mediawithout face-to-face interactions. The aims of this writing are to identify the process ofagreements in e-commerce transactions and to be able to identify the relation betweenthe legal subjective requirements and e-commerce agreements entered by minor legalsubject. The normative legal research is applied in this writing by using secondary dataand legislation approach. There is “offer and acceptance” process in e-commerce2agreements found in this research and in term of e-commerce agreement abrogation,only parents or guardians could ask for abrogation to the judge if minor legal subject iswilling to cancel the agreement. In other word, an e-commerce agreement will remainvalid for both sides if there is no abrogation submitted by parents or guardians.
Keywords: Subjective Requirements, Agreement, Indonesian Civil Code, ECommerce